2001
DOI: 10.4314/eamj.v78i7.9014
|View full text |Cite
|
Sign up to set email alerts
|

Attitude and social consequences of tuberculosis in Addis Ababa, Ethiopia

Abstract: Objective: To gain a better understanding of the attitude and social consequences of tuberculosis (TB) in Addis Ababa, Ethiopia. Design: A cross sectional survey using a structured questionnaire and a qualitative study based on the focus group discussion (FGD) technique. Setting: Eight different kebeles (urban dwellers' associations) of six woredas (next higher administrative level to kebele). Subjects and methods: Seven hundred and three participants, comprising 326 males and 377 females were interviewed usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
7
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 6 publications
3
45
7
1
Order By: Relevance
“…Gelaw et al [12] find that stigmatisation and social exclusion of TB patients are fuelled by the failure of the Male patients often worried about economic problems, while female patients worried about social consequences of the disease. Both in the family and the community, isolation could be subtle, but it could also be obvious and had a tendency to continue much longer than medically justified Rajeswari et al [16] India Focus group discussions and interviews (n = 304 patients, n = 17 focus groups) 34 % of patients reported that due to loss of income they could not afford to buy adequate food or clothing or books for their children.…”
Section: Resultsmentioning
confidence: 99%
“…Gelaw et al [12] find that stigmatisation and social exclusion of TB patients are fuelled by the failure of the Male patients often worried about economic problems, while female patients worried about social consequences of the disease. Both in the family and the community, isolation could be subtle, but it could also be obvious and had a tendency to continue much longer than medically justified Rajeswari et al [16] India Focus group discussions and interviews (n = 304 patients, n = 17 focus groups) 34 % of patients reported that due to loss of income they could not afford to buy adequate food or clothing or books for their children.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the study did not find any discriminatory attitude from families toward the patients, showing much support and continuity of care. A remark that must be registered, however, which has already been documented in another study about attitudes, is that the answers provided by the participants may be those socially acceptable and do not reflect accurately their points of view 35 . Such bias is difficult to control in studies using the object.…”
Section: Discussionmentioning
confidence: 99%
“…Although there were some studies which identified the social effects of tuberculosis, we couldn't found any study to determine the psychosocial adjustment to illness of active tuberculosis patients in the literature [4,5,[11][12][13][14]. Negative behaviours as stigmatization, isolation, etc.…”
Section: Discussionmentioning
confidence: 99%